Novel Antifungal Activity for the Lectin Scytovirin: Inhibition of Cryptococcus neoformans and Cryptococcus gattii - Jones, Tyler H.; McClelland, Erin E.; McFeeters, Hana; McFeeters, Robert L. (Frontiers in Microbiology, 2017)
Pathogenic cryptococci are encapsulated yeast that can cause severe meningoencephalitis. Existing therapeutic options are dated and there is a growing need for new alternative antifungal agents for these fungi. Here we report novel inhibition of pathogenic cryptococci by the antimicrobial lectin Scytovirin. Inhibition was most potent against C. neoformans var neoformans and C. gattii, with MFC values of 500 nM. Scytovirin binding was localized to the cell wall and shown to affect capsule size and release. No effect was observed on melanization or with cells grown in the presence the cell wall stressor Congo red. Synergy which existing antifungals was indicated, most strongly for amphotericin B. Overall, Scytovirin serves as a much needed new avenue for anticryptococcal development.